Heritage-Based Urban Development - Matthias Ripp; Jonquille Clifford (Encyclopedia, 2025)
The purpose of this entry is to introduce the concept of Heritage-based Urban Development and explain its evolution and implications for historic urban landscapes. The term Historic Urban Landscape (HUL) refers to an integrated understanding of historic cities that goes beyond individual monuments or architectural ensembles to encompass the broader spatial, cultural, and functional relationships within the urban fabric. It reflects a shift toward viewing historic areas as dynamic systems with a role in sustainable development. Heritage-based urban development refers to development approaches that take urban heritage—typically within historic urban landscapes—as the starting point, valuing these landscapes in all their specificities, processes, and cultural meanings as resources to be embraced rather than obstacles to be overcome.